An Analysis of Maslow’s Hierarchy of Needs in Levon Cade’s Character in A Working Man (2025) - Latifa Noviana; Dewi Wulan Sari (Jurnal Ilmiah Multidisiplin, 2026)
This study analyzes the hierarchy of needs reflected in Levon Cade, the main character of A Working Man (2025). The research is grounded in Abraham Maslow’s theory of human motivation, which classifies human needs into five levels: physiological needs, safety needs, love and belongingness needs, esteem needs, and self-actualization needs. This study employed a descriptive qualitative method, with the data taken from selected scenes, dialogues, actions, and visual expressions of Levon Cade in the movie. The data were collected through repeated viewing, scene identification, screenshot documentation, and classification based on Maslow’s theoretical framework. The findings reveal that all five levels of needs are reflected in Levon Cade’s character. A total of 23 data were identified, consisting of 8 data of physiological needs, 5 data of safety needs, 4 data of love and belongingness needs, 4 data of esteem needs, and 2 data of self-actualization needs. The most dominant need is physiological need, showing Levon’s effort to maintain basic survival amid conflict and danger. Meanwhile, the fulfillment of safety, belongingness, esteem, and self-actualization needs reflects his struggle to build a stable life, maintain meaningful relationships, gain recognition, and achieve personal fulfillment. This study indicates that Levon Cade’s character development represents the dynamic process of fulfilling human needs in challenging social and personal circumstances.